2022
DOI: 10.3171/2021.1.jns204078
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of 1-stage clipping of multiple unruptured intracranial aneurysms via keyhole approaches

Abstract: OBJECTIVE Complete exclusion of multiple unruptured intracranial aneurysms (UIAs) in one session of intervention may be ideal. However, such situations are not always feasible in terms of treatment modalities and outcomes. The authors aimed to analyze their experience with 1-stage clipping of multiple UIAs. METHODS Medical records between March 2013 and December 2018 were retrospectively reviewed, and 111 1-stage keyhole approaches in 110 patients with 261 multiple UIAs were ultimately included in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, with respect to neurological deterioration at discharge, these parameters did not reach statistical significance and are in line with the results of smaller series. 29,30 Presumably, the risks of simultaneous clipping of multiple aneurysms are additive, and it can be assumed that this additive effect is similar to the risk of a 2-stage procedure and the then respective risks of the individual operations.…”
Section: Discussionmentioning
confidence: 99%
“…However, with respect to neurological deterioration at discharge, these parameters did not reach statistical significance and are in line with the results of smaller series. 29,30 Presumably, the risks of simultaneous clipping of multiple aneurysms are additive, and it can be assumed that this additive effect is similar to the risk of a 2-stage procedure and the then respective risks of the individual operations.…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al [ 14 ] found that one-stage multiple craniotomies for MIAs was safe and economical. Hong et al [ 15 ] also demonstrated that one-stage clipping of MIAs showed satisfactory treatment outcomes. Andic et al [ 16 ] believed that one-stage MIA treatment with combined endovascular techniques was technically feasible but that its safety due to relatively high complication rates remained controversial (i.e., because unruptured tiny aneurysms weighted the low annual spontaneous rupture rate and potential surgical risks) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, significant differences in surgical duration between the two groups could affect the QoR in the early postoperative period. Compared to conventional craniotomy, minicraniotomy generally has the advantage of reducing intraoperative loss of cerebrospinal fluid and blood as surgical duration is about half as short [ 8 , 16 , 27 , 28 ]. However, long surgical duration in the SNB group may have offset these advantages of minicraniotomy, causing greater discomfort and hindering early ambulation after surgery, and may have ultimately counterbalanced the benefits of SNB on postoperative QoR [ 31 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach for clipping of UIAs was based on the location and direction of the aneurysms, spatial relationship among the aneurysms, brain parenchyma, and bony structures, and neurosurgeon’s preference. Four types of keyhole minicraniotomy were considered : supraciliary supraorbital, frontolateral supraorbital, lateral supraorbital, and minipterional approaches [ 8 , 16 ]. Surgical complications, including intraoperative premature aneurysmal rupture and postoperative stroke with neurological deficit, were recorded if present.…”
Section: Methodsmentioning
confidence: 99%